Dual neonate vaccine platform against HIV-1 and M. tuberculosis. - Hopkins, R; Bridgeman, A; Joseph, J; Gilbert, S; McShane, H; Hanke, T (Public Library of Science, 2011)
Acquired immunodeficiency syndrome and tuberculosis (TB) are two of the world's most devastating diseases. The first vaccine the majority of infants born in Africa receive is Mycobacterium bovis bacillus Calmette-Guerin (BCG) as a prevention against TB. BCG protects against disseminated disease in the first 10 years of life, but provides a variable protection against pulmonary TB and enhancing boost delivered by recombinant modified vaccinia virus Ankara (rMVA) expressing antigen 85A (Ag85A) of M. tuberculosis is currently in phase IIb evaluation in African neonates. If the newborn's mother is positive for human immunodeficiency virus type 1 (HIV-1), the baby is at high risk of acquiring HIV-1 through breastfeeding. We suggested that a vaccination consisting of recombinant BCG expressing HIV-1 immunogen administered at birth followed by a boost with rMVA sharing the same immunogen could serve as a strategy for prevention of mother-to-child transmission of HIV-1 and rMVA expressing an African HIV-1-derived immunogen HIVA is currently in phase I trials in African neonates. Here, we aim to develop a dual neonate vaccine platform against HIV-1 and TB consisting of BCG.HIVA administered at birth followed by a boost with MVA.HIVA.85A. Thus, mMVA.HIVA.85A and sMVA.HIVA.85A vaccines were constructed, in which the transgene transcription is driven by either modified H5 or short synthetic promoters, respectively, and tested for immunogenicity alone and in combination with BCG.HIVA(222). mMVA.HIVA.85A was produced markerless and thus suitable for clinical manufacture. While sMVA.HIVA.85A expressed higher levels of the immunogens, it was less immunogenic than mMVA.HIVA.85A in BALB/c mice. A BCG.HIVA(222)-mMVA.HIVA.85A prime-boost regimen induced robust T cell responses to both HIV-1 and M. tuberculosis. Therefore, proof-of-principle for a dual anti-HIV-1/M. tuberculosis infant vaccine platform is established. Induction of immune responses against these pathogens soon after birth is highly desirable and may provide a basis for lifetime protection maintained by boosts later in life.